Long-term Outcomes of Laparoscopic Versus Open Transhiatal Approach for the Treatment of Esophagogastric Junction Cancer - Lee, Yoontaek (J Gastric Cancer, 2019)
PURPOSE: The laparoscopic transhiatal approach (LA) for adenocarcinoma of the esophagogastric junction (AEJ) is advantageous since it allows better visualization of the surgical field than the open approach (OA). We compared the surgical outcomes of the 2 approaches. MATERIALS AND METHODS: We analyzed 108 patients with AEJ who underwent transhiatal distal esophagectomy and gastrectomy with curative intent between 2003 and 2015. Surgical outcomes were reviewed using electronic medical records. RESULTS: The LA and OA were performed in 37 and 71 patients, respectively. Compared to the OA, the LA was associated with significantly shorter duration of postoperative hospital stay (9 vs. 11 days, P=0.001), shorter proximal resection margins (3 vs. 7 mm, P=0.004), and extended operative times (240 vs. 191 min, P=0.001). No significant difference was observed between the LA and OA for intraoperative blood loss (100 vs. 100 mL, P=0.392) or surgical morbidity rate (grade≥II) for complications (8.1% vs. 23.9%, P=0.080). Two cases of anastomotic leakage occurred in the OA group. The number of harvested lymph nodes was not significantly different between the LA and OA groups (54 vs. 51, P=0.889). The 5-year overall and 3-year relapse-free survival rates were 81.8% and 50.7% (P=0.024) and 77.3% and 46.4% (P=0.009) for the LA and OA groups, respectively. Multivariable analyses revealed no independent factors associated with overall survival. CONCLUSIONS: The LA is feasible and safe with short- and long-term oncologic outcomes similar to those of the OA.